Research on optimal strategy of different fire rescue tasks based on oxygen consumption - Tang, Jinyong; Zhang, Xinxin; Wang, Ziwen; Liang, Tiehuai; Liu, Weiguo (Frontiers in Physiology, 2025)
ObjectiveThe development of effective rescue strategies is critical for enhancing rescue operations and ensuring firefighter safety. However, limited attention has been given to the exploration of rational rescue strategies in practice, particularly with regard to oxygen consumption. Therefore, this study aimed to identify the optimal rescue strategy by analyzing oxygen consumption across different rescue tasks.MethodsSixty male firefighters from the Guilin Fire and Rescue Detachment participated in the study. Their oxygen consumption was measured during the completion of running on flat ground and while running up and down three flights of stairs.ResultsThe results found that firefighters with excellent strength and conditioning levels, those carrying a 10 kg load, or those employing the shoulder-carrying technique had less oxygen consumption. Hand-carrying for a 10 kg load when running up or downstairs and shoulder-carrying for 20 and 30 kg loads while running on the ground resulted in lower oxygen consumption. Additionally, firefighters with excellent strength performance when running with 10 and 20 kg loads or those with excellent speed while running on the ground exhibited decreased oxygen consumption.ConclusionThe current study suggests that firefighters with excellent strength performance are more suited for upstairs rescue tasks, while those with excellent speed performance are better suited for tasks on ground. It is recommended that medium to large loads be carried using the shoulder-carrying technique, and smaller loads be hand-carried when running up or down stairs. Overall, customizing rescue strategies based on firefighters’ strength and conditioning, load characteristics, techniques, and specific task requirements is crucial for improving efficiency and reducing risks in rescue operations.